Advertisement call of Dendropsophus oliveirai (Anura, Hylidae) - Santana, Diego José; Mesquita, Daniel Oliveira; Garda, Adrian Antonio (Zootaxa, 2011)
The Dendropsophus decipiens clade is part of the Dendropsophus microcephalus group sensu Faivovich et al. (2005). As far as known, the clade is currently composed of four related species (D. decipiens, D. berthalutzae, D. haddadi, and D. oliveirai) distributed in eastern Brazil, all of which deposit eggs on leaves overhanging water bodies (Faivovich et al. 2005). Dendropsophus oliveirai is a typical species of open areas in the Caatinga and Atlantic Forest of northeastern Brazil (Bastos and Skuk, 2004; Santana et al. 2008).